ICCS 2017 Workshop on Agent-Based Simulations, Adaptive Algorithms and Solvers - Byrski, A.; Paszynski, M.; Schaefer, R.; Calo, Victor; Pardo, D. (2017)
© 2017 The Authors. Published by Elsevier B.V. This workshop seeks to integrate results from different domains of computer science, computational science, and mathematics. We welcome simulation papers, either hard simulations using finite element or finite difference methods, or soft simulations by means of evolutionary computations, and related methods. The workshop focuses on simulations performed by using (a) agent-oriented systems; or (b) adaptive algorithms. Simulations performed by other kind of systems are also welcome. An agent-oriented system seems are attractive tools useful for numerous domains of applications. Adaptive algorithms significantly decrease on the computational cost by investing computational resources when needed by the problem.